Evaluating the efficiency of emergency operation centers during pandemics: a cross-sectional study with operational managers in Iran - Sartipi, Majid; Aminafshar, Asiye; Pakzad, Abdolrazzagh; Shafiei, Mohammadreza; Farahmandnia, Hojjat; Tavan, Asghar (Frontiers in Public Health, 2025)
BackgroundAn effective crisis management system like the Emergency Operations Center (EOC) influences the number of damages and human casualties during disasters and pandemics. This study examined the preparedness and management functions of the Zahedan University of Medical Sciences incident command system (ICS) in response to incidents and disasters, focusing on its implementation during the pandemic.Materials and methodsThe study employed a cross-sectional design. All members of the university’s ICS at various levels were included in the study. The data collection tool was a researcher-made questionnaire. The PCA (Principal component analysis) method was employed in SPSS 27 statistical software for data analysis.ResultsAmong the extracted components, the highest mean was associated with the command and empowerment of operational teams (C2), with a mean of 3.72 (CI: 3.04–4.40). The managers working in the crisis management headquarters, at the planning and comprehensive command level, performed better than other management levels. A significant relationship was found between past crisis experience and the scores of all extracted components. Individuals who had previously been involved in crises scored higher. The p-values for components 1 to 4 were 0.002, 0.001, 0.005, and 0.019, respectively. In C1 (Comprehensive risk planning) and C2, individuals with higher education obtained better scores, 3.85 (CI: 3.15–4.55) and 3.92 (CI: 3.22–4.62) compared to individuals with lower education 3.46 (CI: 2.79–4.13) and 3.57 (CI: 2.93–4.21) (p-values 0.011 and 0.02, respectively). Also, continuous training significantly helped improve the performance of managers. Other variables such as field of study, type of employment, and job history did not show significant differences.ConclusionPast experiences significantly impact people’s ability to prepare and make quick decisions in times of crisis. It is essential to provide effective solutions to future managers and implement corrective measures within the crisis management system. Additionally, training and empowerment programs should be planned for all healthcare workers, and greater attention should be paid to investing in young forces.